PUCAKO COFFEE ROASTERY WEBSITE DESIGN USING AGILE METHOD - Nasution, Isti Nur Fadhilah; Elhanafi, Andi Marwan (Cattleya Darmaya Fortuna, 2025)
The development of online sales has undergone significant transformation in line with advancements in technology and changes in consumer behavior. Online sales have now become an integral part of daily life, with continued growth projections driven by improvements in internet infrastructure and the convenience of digital payment methods. Website-based technology allows companies to offer products without spatial and temporal limitations, providing ease for entrepreneurs to market products and manage sales data. SMEs (Small and Medium Enterprises) take advantage of this opportunity to expand their market and improve their business operations. Pucako Coffee Roastery, as one of the SMEs producing roasted coffee beans in Medan, faces challenges in product marketing limited to offline sales. This results in difficulties for consumers outside the city to purchase products, as well as limited promotional media and transaction management. To address this, this research aims to design a product sales website using the Agile method, which enables product information to be more easily accessed by consumers and helps Pucako Coffee Roastery develop its business more efficiently. By applying the Extreme Programming method in website development, it is expected that the system built will meet information needs and expedite the transaction process, thus enhancing business competitiveness in an increasingly global and competitive market.